Ethological Observations at an Outdoor Gilts Keeping System - Alexy, Márta; Nagy, Géza; Gundel, János (Acta Agraria Debreceniensis, 2004)
The authors examinated behaviour of twenty-eight, grouped-housed Hungarian large white x Hungarian landrasse gilts in grassland-based production system. The social rank was recorded on two days following, social rank was unaffected by even age or weight of gilts. The daily liferhythm was recorded on four different days in two weeks period. Within daily rhyhtm the following behaviours were recorded: eating, drinking, grazing, rooting, excretion and resting. On the first two observation days gilts were more active, in their daily activity two pitches were recorded. 30% of the whole paddock was used specifically by pigs as resting and excretion area.